Plasmodium Falciparum Malaria and Severe Dengue Coinfection in a Pulmonary Tuberculosis Patient: Case Report and Literature Review - Fernando, Mino-Bernal Jorge; Camilo, Martinez Juan; Angela, Montenegro Ibarra (Archives of Clinical and Medical Case Reports, 2018)
Malaria and dengue are the most prevalent vector-borne infections in the world. The clinical manifestations of the two pathologies are similar which may complicate the diagnosis of concurrent dengue and malaria. Coinfection causes a clinical picture of greater severity taking into account the proinflammatory state with capillary leakage and alteration of the glucocalix that is triggered. We present the case of an adult patient with coinfection due to malaria and dengue who is also diagnosed with tuberculosis and required management in the intensive care unit due to multiorgan failure.